Bridging, switching or drug holidays – how to treat a patient who stops natalizumab? - Havla J; Kleiter I; Kümpfel T (Dove Medical Press, 2013)
Joachim Havla,1 Ingo Kleiter,2 Tania Kümpfel11Institute of Clinical Neuroimmunology, Medical Campus Grosshadern, Ludwig Maximilians University, Munich, 2Department of Neurology, St Josef Hospital, Ruhr University, Bochum, GermanyAbstract: Natalizumab (NAT) was the first monoclonal antibody to be approved for the treatment of relapsing-remitting multiple sclerosis (RRMS). While pivotal and post-marketing studies have showed considerable and sustained efficacy of NAT in RRMS, the increasing incidence of therapy-associated progressive multifocal leukoencephalopathy (PML), a brain infection caused by the John Cunningham virus (JCV), is a risk associated with long-term therapy. The risk for therapy-associated PML is highest in so-called “triple risk” patients. Therefore, long-term NAT-treated, immunosuppressive-pretreated, and JCV antibody-positive patients often discontinue NAT therapy. However, until now, it is not known which treatment strategy should be followed after NAT cessation. Since disease activity returns to pretreatment levels, or even above, within 4–7 months from the last infusion of NAT, patients who stop NAT are at considerable risk of relapse and worsening of multiple sclerosis (MS)-related disability. Several strategies have been applied to prevent the recurrence of disease activity after discontinuation of NAT. Of these, bridging with intravenous methylprednisolone, and switching to glatiramer acetate or interferon beta (IFN-beta) do not seem to be effective enough. More promising results have been obtained in retrospective studies and case series with fingolimod (FTY), an alternative escalation therapy for RRMS, although some patients have showed a severe disease rebound after starting FTY treatment. The time interval between the discontinuation of NAT and the start of FTY might affect the recurrence of disease activity. Long-term data about the efficacy and safety of FTY treatment after cessation of NAT are urgently needed and should be further investigated. Prospective studies are warranted, to optimize treatment strategies for RRMS patients who discontinue NAT, especially because new therapies will be available in the very near future.Keywords: natalizumab discontinuation, switching, bridging, drug holidays, multiple sclerosis